Kajian Ruang Terbuka Taman Simpang Polda Palembang - Nafiza, Fadilah; Nasrah, Muhammad; Rofiqoh, Azzahra; Ifafah, Farhany Aura; Cahyani, Regita Dwi; Kamil, Erfan M (Jurnal TekstuReka, 2023)
Through this research, a thorough exploration of various aspects was carried out, including the physical design of the park, usage patterns by the community, and their perceptions of the open space. Research methods involving surveys and observations allow a more comprehensive understanding of the dynamics that occur within the park. The results of the analysis provide an in-depth understanding of the challenges and opportunities faced in efforts to improve the quality of public open spaces, especially in the context of the Simpang POLDA Park. Factors such as object design, accessibility, use, and basic function patterns are the main focus in evaluating positive or negative impacts on park use by local communities. The implications of this research finding can be a basis for designing more effective policies in maximizing the social benefits of public open spaces in cities.